Chronic tobacco smoking, impaired reward-based decision-making, and role of insular cortex: A comparison between early-onset smokers and late-onset smokers - Conti, Aldo Alberto; Baldacchino, Alexander Mario (Frontiers in Psychiatry, 2022)
Introduction: The literature suggests that tobacco smoking may have a neurotoxic effect on the developing adolescent brain. Particularly, it may impair the decision-making process of early onset smokers (<16 years), by rendering them more prone to impulsive and risky choices towards rewards, and therefore more prone to smoking relapses, in comparison to late onset smokers (≥16 years). However, no study has ever investigated reward-based decision-making and structural brain differences between early onset smokers and late onset smokers . Methods: Computerized measures of reward-based decision making [Cambridge Gambling Task, (CGT); 5 Trials Adjusting Delay Discounting Task (ADT-5)] were administered to 11 early onset smokers (mean age at regular smoking initiation=13.2 years), 17 late onset smokers (mean age at regular smoking initiation=18.0 years), and 24 nonsmoker controls. Voxel Based Morphometry (VBM) was utilised to investigate gray matter (GM) and white matter (WM) volume differences in fronto-cortical and striatal brain regions between early onset smokers ,late onset smokers, and nonsmokers . Results: Early onset smokers displayed a riskier decision-making behaviour in comparison to nonsmokers as assessed by the CGT (p<0.01, Cohen's f = 0.48). However, no significant differences (p>0.05) in reward-based decision-making were detected between early onset smokers and late onset smokers. VBM results revealed early onset smokers to present lower GM volume in the bilateral anterior insular cortex (AI) in comparison to late onset smokers, and lower WM volume in the right AI in comparison to late onset smokers. Conclusion: Impairments in reward-based decision-making may not be affected by tobacco smoking initiation during early adolescence. Instead, lower GM and WM volume in the AI of early onset smokers may underline a vulnerability to develop a compulsive tobacco seeking and smoking behaviour during adulthood.